Answer:
(-13, -3)
Step-by-step explanation:
Elimination is used to get either the y or the x to cancel out in both equations. In this case, you'd have to multiply the first equation by -3, so it would be 9x + 21y = -54. Now that you did that, you can "subtract" the two equations. 9x - 9x = 0 (they cancel each other out). 21y - 2y = 19y. -54 - 3 = -57. Now that we're left with 19y = -57, let's find out what y is by solving out the equation. The answer would be y = -3. Now that we have this info, we can substitute the y in one of the two equations to find the x. I'm going to use the first equation. -3x - 7(-3) = 18 --> -3x + 21 = 18 --> -3x = 39. The result is x = -13. Therefore, the answer is (-13, -3).